Assessing the Impact of Accounting Perceptions on Accounting Major Choice Based on Students' Personal Characteristics - Robert Horvat; Nika Pučko (Naše gospodarstvo/Our economy, 2025)
In the paper, the impact of selected popular perceptions about accounting and the accounting major on the accounting major choice was assessed for the sample of undergraduate business school freshmen. Rather than observing differences between accounting majors' and non-accounting majors' perceptions themselves, a novel approach was used, focused on the observation of differences between accounting majors' and non-accounting majors' personal characteristics, deemed as relevant for their fit with selected popular accounting perceptions. Regression coefficients obtained from regressing these personal characteristics on the accounting major choice variable were used as evidence for the impact of observed accounting perceptions on accounting major choice. Results suggest an important impact of some of the popular accounting perceptions on students' decision whether to major in accounting or not.